A review of JAK–STAT signalling in the pathogenesis of spondyloarthritis and the role of JAK inhibition. (20th October 2021) - McInnes, Iain B; Szekanecz, Zoltán; McGonagle, Dennis; Maksymowych, Walter P; Pfeil, Alexander; Lippe, Ralph; Song, In-Ho; Lertratanakul, Apinya; Sornasse, Thierry; Biljan, Ana; Deodhar, Atul
Abstract: Spondyloarthritis (SpA) comprises a group of chronic inflammatory diseases with overlapping clinical, genetic and pathophysiological features including back pain, peripheral arthritis, psoriasis, enthesitis and dactylitis. Several cytokines are involved in the pathogenesis of SpA, variously contributing to each clinical manifestation. Many SpA-associated cytokines, including IL-23, IL-17, IL-6, type I/II interferon and tumour necrosis factor signal directly or indirectly via the Janus kinase (JAK)–signal transducer and activator of transcription pathway. JAK signalling also regulates development and maturation of cells of the innate and adaptive immune systems. Accordingly, disruption of this signalling pathway by small molecule oral JAK inhibitors can inhibit signalling implicated in SpA pathogenesis. Herein we discuss the role of JAK signalling in the pathogenesis of SpA and summarize the safety and efficacy of JAK inhibition by reference to relevant SpA clinical trials.